Voicing Oppression and Abuse: An Intersectional Feminist Reading of Figurative Language in Angelou’s “Still I Rise” - Dimas Satria Pranata; Ruly Indra Darmawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines how figurative language in Maya Angelou's poem “Still I Rise” reflects the experiences of oppression and abuse endured by African-American or Black women. Using Bell Hooks' intersectional feminist theory of interlocking systems of oppression, such as racism, sexism, and classism, the analysis focuses on metaphor, simile, sarcasm, and repetition as literary tools of resistance. Using qualitative descriptive methods, this study identifies and interprets figurative devices in relation to Angelou's life experiences and the broader historical context of Black women’s marginalization. The results reveal that 19 instances of Angelou's figurative language, namely 8 metaphors, 6 similes, 4 sarcasms, and 1 repetition, not only assert identity and resilience but also reveal emotional, psychological, and systemic abuse disguised as cultural or historical narratives. This study contributes to feminist literary discourse by demonstrating how poetic language becomes a site of power and ideological resistance, affirming the enduring relevance of intersectional feminist perspectives in literary analysis.